Dialysis adequacy in chronic hemodialysis patients in Shohada Ashayer Hospital, Khorramabad, Lorestan, Iran - Azita Zafar Mohtashami (Yafteh, 2017)
Background : Chronic kidney disease is an important health issue that its prevalence is increasing both in the worldwide and in our country.